Brincar Heurístico e o Cesto dos Tesouros - A Abordagem à Brincadeira Espontânea em Contextos de Creche - Almeida, Ana (2020)
The following study presents Heuristic Play (HP) and Treasure Basket (TB) as an approach to the importance of heuristic play in early childhood education. The present research had as a primary goal to answer the following questions: • What does Heuristic Play consist of and how can it be applied? • In what ways does Heuristic Play influences children in their development in their early years of life? • What were the appreciations of the nursery schoolteachers concerning the Heuristic Play method? From these questions, we defined three objectives for this research: • Knowing HP in early childhood education; • Recognizing how HP influences child development; • Understanding how education professionals see HP. In this research, the concept of the HP method is presented, and how it has a promotor role in child development. It is theoretically substantiated, mentioning the theories of reference in this field and its importance in the context of education. This research is qualitative in nature, guiding itself by naturalist observations of children between eight months old and three years old and by formulating a comprehensive model of the conceptualizations (beliefs and implicit theories) of a group of nursery schoolteachers regarding this subject. Through this research, we ascertained that HP is a relevant method to the psychosocial, cognitive and motor developments of children, contributing to a ludic and pleasurable learning.